Retinoblastoma. Part 1. Clinical presentations and diagnostic tools - S.V. Ivanova; S.A. Kuleva; N.N. Sadovnikova; M.I. Komissarov; M.N. Chistyakova; A.V. Khokhlova; N.A. Shchegoleva (РМЖ "Клиническая офтальмология")
Retinoblastoma. Part 1. Clinical presentations and diagnostic tools S.V. Ivanova1, S.A. Kuleva1, N.N. Sadovnikova2, M.I. Komissarov2, M.N. Chistyakova2, A.V. Khokhlova1, N.A. Shchegoleva3 1N.N. Petrov National Medical Research Center of Oncology, St. Petersburg,  Russian Federation 2St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation 3K.A. Rauchfuss St. Petersburg Children’s City Multidisciplinary Clinical Center of High Medical Technologies, St. Petersburg, Russian Federation Retinoblastoma is one of the most common retinal tumors in young children. At the time of primary diagnosis, mean age is no more than 1.5 years. The association between tumor development and the loss of both alleles of RB1 gene is well-established. Mutations in the RB1 gene result in the complete inactivation of retinoblastoma protein expression and, therefore, uncontrolled cell proliferation and generation of tumor cell clone. There are two types of retinoblastoma, i.e., hereditary and sporadic. This paper describes in detail clinical epidemiological characteristics of hereditary and sporadic retinoblastoma and major clinical signs (in particular, one of the most early and common symptoms, leukocoria). Histology of malignant tumor and its benign precursor is addressed. Current classification systems of intraocular retinoblastoma are based on tumor extent being required to specify clear indications for organ preservation treatment. Modern diagnostic tools for retinoblastoma are discussed as well. Eye fundus examination is the gold standard but has some specifics in young children. Other important imaging techniques in retinoblastoma are sonography, optical coherence tomography, and magnetic resonance imaging. Keywords: children, retinoblastoma, heredity, retinoblastoma gene, pathomorphology, leukocoria, ophthalmoscopy, sonography. For citation: Ivanova S.V., Kuleva S.A., Sadovnikova N.N. et al. Retinoblastoma. Part 1. Clinical presentations and diagnostic tools. Russian Journal of Clinical Ophthalmology. 2020;20(3):159–164. DOI: 10.32364/2311-7729-2020-20-3-159-164.